Book Review: Scalable and Secure Internet Services and Architecture. (2nd May 2007) - He, Xubin
Scalable and Secure Internet Services and Architecture, by Chengzhong Xu. Chapman & Hall/CRC, 2005. ISBN 1-58488-377-4